(3cJGH GdeYQaI aj GdeSGFd GdGYJbGOjIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3GdMeO ddg hGgH GdCSQGQ GdCQHGH GdeTGgOGJ hGdCHUGQ aUd CeG HYO aEf ddYbhd MOG Jba YfOg ef MjK eG gi eacQI dG ef MjK eG gi bGHdI s
(3BNQgG (B:s
(3aeOGQ GdeYQaI Ydi GdMbjbi Ydi Yde KdGK , Yde GdCdhgjI , Yde GdPGJ , hYde fSHI gPg GdGdhgjI dgPg GdPGJ , hHYO gPG cdg adG EMGWI hdG EOQGc , hGddg jbhd GdMb hgh jgOi GdSHjd Je HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B13 - (3U(B25s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG ebGHdI hJUMjM SfI (B1084(3g` hYdjgG JbjjOGJs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs